Al-Ghazali's Ethics in Supporting Character Education The Perspective of the Manggarai Community through Uwa Haeng Wulang Langkas Haeng Ntala - Yulianus Gunawan Mamput (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
This article discusses the correlation between the local wisdom of the Manggarai community expressed in the proverb "uwa haeng wulang langkas haeng ntala" and the ethical concepts of Imam Al-Ghazali in the context of character education. "Uwa haeng wulang langkas haeng ntala," an ancient proverb of the Manggarai people, teaches the spirit of reaching for aspirations as high as the sky. Meanwhile, Al-Ghazali's ethics emphasizes character formation through moral values and justice, with a focus on the noble goal of eternal happiness in the afterlife. This article examines how these two thoughts can be integrated to strengthen character education in self-development. The practical implications of this connectivity discuss the challenges and benefits of character education, as well as how local values can complement universal ethical concepts.